2005
DOI: 10.1097/01.sla.0000184169.73614.09
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Trauma Center Designation and Trauma Volume on Outcome in Specific Severe Injuries

Abstract: Level I trauma centers have better outcomes than lower-level centers in patients with specific injuries associated with high mortality and poor functional outcomes. The volume of major trauma admissions does not influence outcome in either level I or II centers. These findings may have significant implications in the planning of trauma systems and the billing of services according to level of accreditation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
227
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 354 publications
(237 citation statements)
references
References 20 publications
7
227
0
3
Order By: Relevance
“…Using National Trauma Data Bank (NTDB) data from 1994-2003, one group found significantly lower mortality among patients age 14 or older treated for severe traumatic injuries at Level I trauma centers compared with patients treated at Level II centers. 8,9 These findings were consistent with several smaller, state-specific studies, which found significantly lower risk of mortality among all adult trauma patients treated at Level I centers in Pennsylvania 10 and Ohio 11 compared with those treated at Level II centers. Conversely, one study focused on isolated patients with severe TBI of all ages in the NTDB found no significant difference in mortality between American College of Surgeons (ACS) Level I and II trauma centers.…”
Section: Introductionsupporting
confidence: 87%
“…Using National Trauma Data Bank (NTDB) data from 1994-2003, one group found significantly lower mortality among patients age 14 or older treated for severe traumatic injuries at Level I trauma centers compared with patients treated at Level II centers. 8,9 These findings were consistent with several smaller, state-specific studies, which found significantly lower risk of mortality among all adult trauma patients treated at Level I centers in Pennsylvania 10 and Ohio 11 compared with those treated at Level II centers. Conversely, one study focused on isolated patients with severe TBI of all ages in the NTDB found no significant difference in mortality between American College of Surgeons (ACS) Level I and II trauma centers.…”
Section: Introductionsupporting
confidence: 87%
“…It is interesting that only 17.7% of the patients had an isolated abdominal injury. However, majority of the patients with abdominal trauma present with thoracic and/or pelvic injuries, [6][7][8] indicating that the management of patients with blunt trauma injuries requires a multidisciplinary approach, including physicians trained in the management of trauma, as well as well-equipped trauma centers. The mortality rate has been reported to be lower in healthcare centers where trauma management is satisfactory.…”
Section: Discussionmentioning
confidence: 99%
“…It is also the major cause of death in individuals aged 5 to 49 sicians and other healthcare staff trained on the management of trauma injuries is available. [6,7] In Turkey, general surgeons are still mostly faced with patients with multi-trauma injuries in State Hospitals, University Hospitals, and Training and Research Hospitals, followed by the request for consultation. These patients may be referred to the related department for additional therapies when their clinical status is stable.…”
Section: Introductionmentioning
confidence: 99%
“…1 In the past 4 decades, regionalized trauma care has been promoted in the U.S. as the best approach for matching patient needs with the available resources and provider expertise to achieve optimal patient outcomes. [2][3][4][5] Previous research has shown that trauma centers achieve better outcomes among severely injured patients than non-trauma centers; however, it has been found that about one-third of patients with severe injuries were treated at nontrauma centers or level III trauma centers. 3,6 Transportation to the hospital via Emergency Medical Service (EMS) is important in caring for trauma patients for several reasons.…”
Section: Introductionmentioning
confidence: 99%